Novel Gadis Pantai Karya Pramoedya Ananta Toer sebagai Dasar Penciptaan Skenario - Philipus Nugroho Hari Wibowo (Institut Seni Indonesia Yogyakarta, 2015)
Penciptaan ini mengadaptasi novel Gadis Pantai karya Pramoedya Ananta Toer (Pram) menjadi skenario. Kepiawaian Pram dalam menulis novel tidak diragukan lagi. Banyak karya Pram yang menjadi best seller, dari tangannya lahir karya-karya yang hebat, berbagai penghargaan pernah ia dapatkan, hingga nominasi nobel. Karya Pram sampai saat ini belum ada yang berhasil difilmkan, mungkin masa lalu Pram yang dekat dengan Lekra yang membuat seperti ini. Ide menjadi hal yang paling penting dalam sebuah skenario (film), Ide mengadaptasi novel menjadi pilihan yang jitu. Mengingat banyak film yang memenangkan penghargaan merupakan film adaptasi dari novel-novel best seler.Gadis Pantai Pramoedya Ananta Toer’s Novel as a Basic Scenario Creation. The creation is adapting the novel Gadis Pantai by Pramoedya Ananta Toer into a scenario. There is no doubt about Pram expertise in writing novels, many works of Pram considered as best seller, many great works were born from his hands, he has received the various awards, moreover, he was nominated as a nobel nominee. To this moment, there is no such works of Pram which is successfully filmed,it is probably because in his past time, Pram has been considered as a person who is “near” to LEKRA. An idea becomes the most important thing in making a screenplay (movie), The idea of adapting the novel becomes a workable option. As there have been many films that are also adaptated from the best seller novels.